Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijms21186658
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Non-Coding RNAs (ncRNAs) in Cancer Stem Cell Biology

Abstract: The identification of cancer stem cells (CSCs) as initiators of carcinogenesis has revolutionized the era of cancer research and our perception for the disease treatment options. Additional CSC features, including self-renewal and migratory and invasive capabilities, have further justified these cells as putative diagnostic, prognostic, and therapeutic targets. Given the CSC plasticity, the identification of CSC-related biomarkers has been a serious burden in CSC characterization and therapeutic targeting. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 237 publications
0
12
0
Order By: Relevance
“…CSCs in such a niche are able to maintain their stemness state [30]. On one hand, the niche with hypoxia and high vascular intensity can directly maintain CSCs plasticity and survival [31]. On the other hand, the maintenance of CSCs can be reinforced by the EMT process under such a favorable microenvironment.…”
Section: The Relationship Between Emt and Cscsmentioning
confidence: 99%
“…CSCs in such a niche are able to maintain their stemness state [30]. On one hand, the niche with hypoxia and high vascular intensity can directly maintain CSCs plasticity and survival [31]. On the other hand, the maintenance of CSCs can be reinforced by the EMT process under such a favorable microenvironment.…”
Section: The Relationship Between Emt and Cscsmentioning
confidence: 99%
“…Moreover, to test the accuracy of the workflow across diverse sets of data, we moved to a public dataset. Recent findings have indicated that the role of piRNAs may not be only limited to germ cells, but may be extended to the regulation of cancer, promoting a stem-like state of tumour cells 65 . Therefore, we selected a dataset (GSE68246) to compare the piRNA profiles of breast spheroid-enriched CSCs against parental MCF7 cells and also generated in this case files, statistics and plots with WIND that are all available on the GitHub repository.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, to test the accuracy of the workflow across diverse sets of data, we moved to a public dataset. Recent findings have indicated that the role of piRNAs may not be only limited to germ cells, but may be extended to the regulation of cancer, promoting a stem-like state of tumour cells 61 . Therefore, we selected a dataset (GSE68246) to compare the piRNA profiles of breast spheroid-enriched CSCs against parental MCF7 cells and also generated in this case files, statistics and plots with WIND that are all available on the GitHub repository.…”
Section: Resultsmentioning
confidence: 99%